POLA ANOMALI MAGNET RESIDUAL DARI APLIKASI METODE TREND SURFACE ANALYSIS (TSA), HUBUNGANNYA DENGAN TATAAN GEOLOGI BAWAH DASAR LAUT DALAM PEMETAAN GEOLOGI KELAUTAN BERSISTEM DI PERAIRAN MANADO SULAWESI UTARA - D. Ilhaude; B. Nirwana (Pusat Survei Geologi, 2010)
Analysis of magnetic intensity using a TSA method shows a significant value of residual anomaly from the separation of total magnetic anomaly value. Contour of the residual anomaly resulted from the 2nd order value of regional anomaly is assumed to be correlated with the geological structures of southwest-northeast directions.Keyword: TSA method, residual anomaly